Plasma sprayed zirconia-hydroxyapatite composite coatings - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
In order to overcome the fragility and to improve the physical stability of hydroxyapatite (HA) on the implant, 5, 10, and 15 % yttria stabilized zirconia (YTZP) was added to the starting plasma spraying HA powder Metco XPT-D-703. From the recent literature it is already known that HA coatings tend to dissolve in body fluid environment. To decrease the dissolution effect many additives like zirconia (Zr) could be added to HA powder. In this study, prepared RA composite powders were sprayed onto titanium (Ti) surfaces with a Metco plasma gun. As a control group, pure HA powder was sprayed onto other Ti samples. All samples were subjected to tensile tests according to the ASTM C-633-79. SEM images were taken using back-scattering from prepared cross-sections. X-ray diffraction images were taken from the surface. It was seen that with the increase of the Zr content, the tensile test values increased. Pure HA showed also that the addition of Zr had improved the tensile bond strength (TBS) values.
Keywords: hydroxyapatite; zirconia; plasma spraying; composite; TITANIUM